Sistem Informasi Penjualan Handpone Pada Toko Delta Cellular - Zahara, Rita; Abdussalam; Imilda (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2023)
Conventional trading, where sellers and buyers meet at certain locations to carry out transactions, is increasingly being abandoned with technological developments. One of the innovations that has emerged is e-commerce. E-commerce allows buying and selling transactions online, freeing from geographical limitations. In this research, attention is limited to the Design of a Mobile Phone Sales Information System at the Delta Cellular Store. The purpose of this research is to understand the information system for selling cellphones at the shop and design a web-based information system for selling cellphones. The research results show that this Mobile Sales Application makes it easier to process transaction data and stock of goods. The development methods used include old system analysis, user needs analysis, system feasibility evaluation, process design using the DAD method, data design by designing tables, and user interface design using appropriate designs. This application was built using a web-based programming language with MySQL as the database. The level of accuracy of this application in recording transactions and cellphone stock can be adjusted based on certain time periods, which helps reduce the level of human error. This application can also handle price changes and item additions by allowing users to change this information through the sales transaction form. This application is designed to be simple and uses language that is easy for users to understand, so training in its operation does not require a long time.